2011
DOI: 10.1039/c0cs00023j
|View full text |Cite
|
Sign up to set email alerts
|

Arylspiroboronate esters: from lithium batteries to wood preservatives to catalysis

Abstract: The addition of catechol derivatives to boric acid affords a diverse family of compounds called arylspiroboronate esters. Due to boron's relatively low toxicity towards mammals, arylspiroboronate esters have several biological applications and are active for the treatment of wood against fungi and rot. These compounds are also finding increased use in organic synthesis and in catalysis. This critical review presents the synthesis, properties and applications of these remarkable compounds (149 references).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
29
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 140 publications
(151 reference statements)
2
29
0
Order By: Relevance
“…As expected, coordination occurs through the two deprotonated phenolic groups of gallic acid and not with the carboxylic acid group. Bond distances and angles are similar to those reported in related arylspiroboron compounds . As observed in related salts, one of the boron oxygen bonds, B(1)―O(2) which is 1.538(3) Å, is slightly longer than the other three which are B(1)―O(1) 1.469(3), B(1)―O(4) 1.474(3), and B(1)―O(3) 1.475(3) Å.…”
Section: Resultssupporting
confidence: 81%
“…As expected, coordination occurs through the two deprotonated phenolic groups of gallic acid and not with the carboxylic acid group. Bond distances and angles are similar to those reported in related arylspiroboron compounds . As observed in related salts, one of the boron oxygen bonds, B(1)―O(2) which is 1.538(3) Å, is slightly longer than the other three which are B(1)―O(1) 1.469(3), B(1)―O(4) 1.474(3), and B(1)―O(3) 1.475(3) Å.…”
Section: Resultssupporting
confidence: 81%
“…[159] Furthermore,t he perfluorinated analogue Li[B(1,2-O 2 C 6 F 4 ) 2 ]has also been reported and demonstrates an increase in conductivity compared to the parent Li[B(cat) 2 ], thus making it of interest for lithium ion batteries. [159] Furthermore,t he perfluorinated analogue Li[B(1,2-O 2 C 6 F 4 ) 2 ]has also been reported and demonstrates an increase in conductivity compared to the parent Li[B(cat) 2 ], thus making it of interest for lithium ion batteries.…”
Section: Other Promising Candidates For Wcasmentioning
confidence: 99%
“…We found that this reaction leads to a mixture of products including the cationic species [cis-Rh(PMePh2)2(NCCH3)2] + and anionic [BC28H40O4] - (1), shown in Fig. 1, where the bulky arylspiroborate ligand does not appear to bind to the metal centre.…”
mentioning
confidence: 95%
“…Metal complexes containing these ligands are active and selective catalyst precursors for a number of reactions, including the hydroboration of alkenes. 1 Our group has been investigating the synthesis and reactivity of novel arylspiroborates and we have recently prepared Tl[B(1,2-O2C6H2-3,5-di-tert-butyl)2]. 2 To examine whether this anion could coordinate to metal centers we added one equivalent of the thallium salt to an acetonitrile solution containing the in situ mixture of [Rh(m-Cl)(coe)2]2 and 4PMePh2 (coe = cyclooctene).…”
mentioning
confidence: 99%
See 1 more Smart Citation